Spatial patterns and characterization of marine litter from sandy beaches facing an urban area and a Marine Protected Area - Corbari, Laura; Berlino, Manuel; Milivojevic, Ana; Botero Angel, Ana Maria; Bosch-Belmar, Mar; Capodici, Fulvio; Ciraolo, Giuseppe; Sarà, Gianluca; Mangano, M. Cristina (Frontiers in Marine Science, 2025)
Marine litter is a globally recognized issue that impacts the environment and has significant negative effects on both human health and socio-economic activities. Mainly composed of plastic items, marine litter can be dispersed in the ocean by surface currents, sink to the seafloor, and/or be deposited on coastal areas. Monitoring, quantifying, and characterizing beach litter can be time-consuming but can be conducted using established monitoring protocols (both European and international) and supported by citizen science. Here, we present and discuss the main outcomes from in situ monitoring campaigns covering sandy beaches in both an urban area and a Marine Protected Area. Both macro- and meso-litter were quantified and identified by material, size, shape, and color. The quantity and heterogeneity of items (classified using the Joint List of Litter Categories for Macrolitter Monitoring) were highest in areas with the greatest user presence (e.g., refreshment areas, shops, and restaurants). Free-access beaches showed the highest density of macro-litter items compared to beaches where entrance was regulated by three levels of subscription. Artificial polymers/plastics, particularly plastic caps and lids, dominated, followed by paper and cardboard fragments. A database has been created allowing to highlight hotspots and patterns of occurrence that can inform local management measures, urging municipalities to improve waste management.